2016
DOI: 10.1002/nbm.3667
|View full text |Cite
|
Sign up to set email alerts
|

Elevated phosphodiester and T2 levels can be measured in the absence of fat infiltration in Duchenne muscular dystrophy patients

Abstract: Quantitative MRI and MRS are increasingly important as non-invasive outcome measures in therapy development for Duchenne muscular dystrophy (DMD). Many studies have focussed on individual measures such as fat fraction and metabolite levels in relation to age and functionality, but much less attention has been given to how these indices relate to each other. Here, we assessed spatially resolved metabolic changes in leg muscles of DMD patients, and classified muscles according to the degree of fat replacement co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
74
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 47 publications
19
74
1
Order By: Relevance
“…We applied a multiparametric MRI protocol including standard and emerging techniques to characterize the different pathological processes observed in a small cohort of DMD patients. In confirmatory fashion, we found that young DMD patients exhibited significant increased water T 2 values . Furthermore, progressive fatty infiltration leads to increased muscular fat deposition in older DMD patients .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We applied a multiparametric MRI protocol including standard and emerging techniques to characterize the different pathological processes observed in a small cohort of DMD patients. In confirmatory fashion, we found that young DMD patients exhibited significant increased water T 2 values . Furthermore, progressive fatty infiltration leads to increased muscular fat deposition in older DMD patients .…”
Section: Discussionsupporting
confidence: 67%
“…Quantitative magnetic resonance imaging (MRI) has been used to describe the natural history of the disease and has been suggested as an outcome measure in clinical trials for DMD. Most of these studies evaluated the fat fraction (FF) and the muscle water T 2 to assess disease severity, progression, and activity . Both methods have limitations: water T 2 changes are nonspecific and are influenced by corticosteroid therapy .…”
mentioning
confidence: 99%
“…The extensor digitorum longus muscle of the DMD participants showed higher muscle fat (%) but had water T 2 values similar to that in the healthy volunteers, whereas the tibialis posterior muscle had higher muscle water T 2 in DMD participants than the healthy volunteers but did not show changes of fatty infiltration. During the preparation of this manuscript, Hooijmans et al also reported an increase in muscle water T 2 in the non-fatty infiltrated lower leg muscles of DMD patients using tri-exponential model [27]. Minor differences in the muscle water T 2 values between studies could be related to differences in the MR acquisition parameters for echo spacing and the length of echo-train, heterogeneity of disease status between patient groups and different steroid dosing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…We found that DMD muscle had a significantly higher muscle fat fraction than controls, where control muscle fat fraction was about 4.5 – 5%. The exact value of control muscle fat fraction can depend on whether the analysis model accounts for noise bias and T2* for example, control muscle fat values reported by Loughran et al [58] measured by incorporated R2* modeling were lower than Hooijmans et al [27], who did not.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo 31 P MRS datasets were obtained from the right lower leg using a 7T MR scanner (Philips, Achieva, Best, The Netherlands) for 23 BMD patients as described before . Metabolite ratios and tissue pH were calculated for muscles individually and then averaged for all muscles.…”
Section: Methodsmentioning
confidence: 99%